Assessing hydrochar wash-water toxicity: screening strategies for reducing toxicity from food waste-derived hydrochars - Andres Sarrion; Jasmine R. Flora; Joseph R.V. Flora; Ramesh Goel; Lubo Liu; Perry J. Pellechia; Elena Diaz; Angel F. Mohedano; Nicole D. Berge (Waste Management, 2026)

Effect of sex, leg dominance, and task on knee cartilage and anterior cruciate ligament biomechanics during single-leg landings-a pilot study - Sara Sadeqi; Grant E. Norte; Amanda Murray; David M. Dueber; Michael D. Toland; Deniz U. Erbulut; Vijay K. Goel (Next Research, 2026)

Deciphering the Role of Nanoparticles Induced Microbial Exopolysaccharides in Soil Amelioration and Plant Health - Ritika Chauhan; Vishnu D. Rajput; Tatiana Minkina; Ram Prasad; Yongguan Zhu; Ajit Varma; Arti Goel (Clean Technologies and Environmental Policy, 2025)

Room for education: Undergraduate students associate plastic surgery primarily with aesthetic procedures - Charlotte R. Reed; Bradley A. Melnick; Gretchen A. O’Connor; Rena A. Li; Tokoya Williams; Chirag Goel; Robert D. Galiano (Next Research, 2025)

Evaluation of environmental impacts of mobile phones in India using life cycle assessment technique - D. Dutta; VR. Sankar Cheela; B. Dubey; S. Kumar; S. Goel (International Journal of Environmental Science and Technology, 2025)

Exploring the insights of bioslurry—Nanoparticle amalgam for soil amelioration - Abhinav Singh; Ritika Chauhan; Vishnu D. Rajput; Tatiana Minkina; Ram Prasad; Arti Goel (Environmental Science and Pollution Research, 2024)

Recycling food waste to agriculture through hydrothermal carbonization sustains food-energy-water nexus - Hao Xu; Tong Chen; Yide Shan; Kang Chen; Ning Ling; Lixuan Ren; Hongye Qu; Nicole D. Berge; Joseph R.V. Flora; Ramesh Goel; Lubo Liu; Zhipeng Liu; et al. (Chemical Engineering Journal, 2024)

Trichoderma Mediated Metal Chelator and Its Role in Solanum melongena Growth Under Heavy Metals - Gaurav Yadav; Neha Sharma; Arti Goel; Ajit Varma; Arti Mishra; S. L. Kothari; D. K. Choudhary (Journal of Plant Growth Regulation, 2024)

Environmental risk factors associated with the survival, persistence, and thermal tolerance of Cronobacter sakazakii during the manufacture of powdered infant formula - Rajni Chauhan; Ben D. Tall; Gopal Gopinath; Wamik Azmi; Gunjan Goel (Critical Reviews in Food Science and Nutrition, 2023)

Deep tubewell use is associated with increased household microbial contamination in rural Bangladesh: Results from a prospective cohort study among households in rural Bangladesh - Varun Goel; Brianna Chan; Mia Ziade; Md. Yunus; Md. Taslim Ali; Md. Al Fazal Khan; Md. Nurul Alam; ASG Faruque; Shahabuddin Babu; Md.Masnoon Kabir; Paul L. Delamater; Marc Serre; et al. (Environmental Pollution, 2023)

Microfluidic electrochemical device for real-time culturing and interference-free detection of Escherichia coli - Sonal Fande; Khairunnisa Amreen; D. Sriram; Sanket Goel (Analytica Chimica Acta, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phosphorus loss assessment tools: a review of underlying concepts and applicability in cold climates - Reza Habibiandehkordi; D. Keith Reid; Pradeep K. Goel; Asim Biswas (Environmental Science and Pollution Research, 2020)
Identifying critical source areas (CSAs) of a watershed by phosphorus (P) loss assessment tools is essential for optimal placement of beneficial management practices (BMPs) to address diffuse P pollution. However, lack of significant progress in tackling diffuse P pollution could be, in part, associated with inefficacy of P loss assessment tools for accurately identifying CSAs. Phosphorus loss assessment tools have been developed to simulate P loss from the landscape where runoff is mainly driven by rainfall events. Therefore, they may underperform in cold climates where the land is often frozen during winter and runoff is dominated by snowmelt. This paper (i) reviews the strengths and weaknesses of current P loss assessment tools and their underlying assumptions in simulating soil P dynamics and P transfer to runoff, and (ii) highlights a number of challenges associated with modeling P transfer from agricultural land to surface waters in cold climates. Current P loss assessment tools do not appear to fully represent hydrological and biogeochemical processes responsible for P loss from CSAs, particularly in cold climates. Effort should be made to develop P loss assessment tools that are capable of considering P dynamics through the landscape as a result of abiotic perturbations that are common in cold climates, predicting runoff and P movement over frozen/partially frozen soils, and considering material-P connectivity between landscape and surface waters. Evaluating P loss assessment tools with water quality data is necessary to ensure such modifications result in improved identification of CSAs.

Prediction of upslope movement of Rhododendron arboreum in Western Himalaya - Sri N. S. Veera; Rajendra M. Panda; Mukunda D. Behera; Shailendra Goel; Partha S. Roy; Saroj K. Barik (Tropical Ecology, 2019)

Psyhcrotolerant Bio-inoculants and Their Co-inoculation to Improve Cicer arietinum Growth and Soil Nutrient Status for Sustainable Mountain Agriculture - Nitin Rawat; Mansi Sharma; Deep Chandra Suyal; D. K. Singh; Divya Joshi; Pranjali Singh; Reeta Goel (Journal of Soil Science and Plant Nutrition, 2019)

Prediction of Ground Behaviour for Rock Tunnelling - R. D. Dwivedi; R. K. Goel; M. Singh; M. N. Viladkar; P. K. Singh (Rock Mechanics and Rock Engineering, 2019)

Insights into direct interspecies electron transfer mechanisms for acceleration of anaerobic digestion of wastes - D. Sharma; R. Mahajan; G. Goel (International Journal of Environmental Science and Technology, 2019)

A novel technique for detoxification of phenol from wastewater: Nanoparticle Assisted Nano Filtration (NANF) - L. D. Naidu; S. Saravanan; Mukesh Goel; S. Periasamy; Pieter Stroeve (Journal of Environmental Health Science and Engineering, 2016)

Water pollution of Sabarmati River—a Harbinger to potential disaster - Soumya Haldar; Subir Kumar Mandal; R. B. Thorat; Sangita Goel; Krushnakant D. Baxi; Navalsang P. Parmer; Vipul Patel; S. Basha; K. H. Mody (Environmental Monitoring and Assessment, 2014)

Occurrence and distribution of selected heavy metals and boron in groundwater of the Gulf of Khambhat region, Gujarat, India - Devang Upadhyaya; Mayur D. Survaiya; Shaik Basha; Subir K. Mandal; R. B. Thorat; Soumya Haldar; Sangita Goel; Himal Dave; Krushnakant Baxi; Rohit H. Trivedi; Kalpana H. Mody (Environmental Science and Pollution Research, 2014)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Transformation of pWWO in Rhizobium leguminosarum DPT to Engineer Toluene Degrading Ability for Rhizoremediation - Garima Goel; Piyush Pandey; Anchal Sood; Sandeep Bisht; D. K. Maheshwari; G. D. Sharma (Indian Journal of Microbiology, 2012)

Highly Expressed Recombinant SEB for Antibody Production and Development of Immunodetection System - Ranu Agrawal; Pawan Kumar Singh; Sushil Kumar Sharma; D. V. Kamboj; Ajay Kumar Goel; Lokendra Singh (Indian Journal of Microbiology, 2012)

Regeneration of Red Cell Cholinesterase Activity Following Pralidoxime (2-PAM) Infusion in First 24 h in Organophosphate Poisoned Patients - Parul Goel; Nidhi Gupta; Surjit Singh; Ashish Bhalla; Navneet Sharma; K. D. Gill (Indian Journal of Clinical Biochemistry, 2012)

Overexpression of osmotin gene confers tolerance to salt and drought stresses in transgenic tomato (Solanum lycopersicum L.) - D. Goel; A. K. Singh; V. Yadav; S. B. Babbar; K. C. Bansal (Protoplasma, 2010)

Limitation of 90 m SRTM DEM in drainage network delineation using D8 method—a case study in flat terrain of Bangladesh - M. M. Rahman; D. S. Arya; N. K. Goel (Applied Geomatics, 2010)

Virulence profile and clonal relationship among the Vibrio cholerae isolates from ground and surface water in a cholera endemic area during rainy season - A. K. Goel; M. Jain; P. Kumar; D. V. Kamboj; L. Singh (Folia Microbiologica, 2010)

Analysis of historical changes in rainfall in the Indian Himalayas - Ashoke Basistha; D. S. Arya; N. K. Goel (International Journal of Climatology, 2009)
The present study attempts to explore changes in rainfall pattern in the Indian Himalayas during 20th century using 80‐year data from 30 rain gauge stations maintained by the India Meteorological Department (IMD). Modified Mann–Kendall test (MMK) was applied to detect trend, and Pettitt–Mann–Whitney (PMW) test was employed to detect possible shift. Implication of the change is discussed in terms of percentage change over mean. The results show that the most probable year of change in annual as well as monsoon rainfall in the region is 1964. There was an increasing trend upto 1964 (corroborating with all India and nearby plains), followed by a decreasing trend in 1965–1980 (exclusive to this region). In the entire region, changes are most conspicuous over the Shivaliks and the southern part of the Lesser Himalayas. Copyright © 2008 Royal Meteorological Society

Spatial Distribution of Rainfall in Indian Himalayas – A Case Study of Uttarakhand Region - Ashoke Basistha; D. S. Arya; N. K. Goel (Water Resources Management, 2008)

Climate Variability Influences on Hydrological Responses of a Large Himalayan Basin - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Single multiplex polymerase chain reaction for environmental surveillance of toxigenic—Pathogenic O1 and Non-O1vibrio cholerae - A. K. Goel; S. Ponmariappan; D. V. Kamboj; L. Singh (Folia Microbiologica, 2007)

Role of zinc in mitigating the toxic effects of chlorpyrifos on hematological alterations and electron microscopic observations in rat blood - Ajay Goel; Vijayta Dani; D. K. Dhawan (BioMetals, 2006)

Spatial Distribution and Seasonal Variability of Rainfall in a Mountainous Basin in the Himalayan Region - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2006)

Detection of Viable Toxigenic Vibrio cholerae from Environmental Water Sources by Direct Cell Duplex PCR Assay - A. K. Goel; A. K. Tamrakar; V. Nema; D. V. Kamboj; L. Singh (World Journal of Microbiology and Biotechnology, 2005)

Direct immunofluorescence assay for rapid environmental detection ofVibrio cholerae O1 - A. K. Goel; A. K. Tamrakar; D. V. Kamboj; L. Singh (Folia Microbiologica, 2005)

A comparative evaluation of culture conditions for short-term maintenance (<24 hr) of human islets isolated using the Edmonton protocol - Shinichi Matsumoto; Shilpa Goel; Sabrina Qualley; D. Michael Strong; Jo Anna Reems (Cell and Tissue Banking, 2003)

The ability of an HSV strain to initiate zosteriform spread correlates with its neuroinvasive disease potential - N. Goel; H. Mao; Q. Rong; J. J. Docherty; D. Zimmerman; K. S. Rosenthal (Archives of Virology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Receptor- ‘Ck’ dependent signalling regulates the LDL-receptor gene transcription - Rajeev Goel; Jarnail Singh; D. Kaul (Molecular and Cellular Biochemistry, 1997)